2018
DOI: 10.1155/2018/5910372
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction after Living-Donor Liver Transplantation: Experience with 500 Cases

Abstract: Introduction. The possible risk factors for chronic kidney disease in transplant recipients have not been thoroughly investigated after living-donor liver transplantation. Material and Methods. A retrospective cohort study of consecutive adults who underwent living-donor liver transplantation between May 2004 and October 2016, in a single center, was conducted. Kidney function was investigated successively for all the patients throughout the study period, with 12 months being the shortest follow-up. Postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In another study by Kim et al [ 31 ], 43.5% of the overall LT recipients were reported to have moderate renal dysfunction (defined as the 30≤ eGFR <60 mL/min/1.73 m 2 ). The rate of renal dysfunction post-LT varies considerably among recipients in other countries, with 8.0% in Egypt [ 33 ], 48.0% in Spain [ 34 ], and 46.7% in Brazil [ 35 ]. This disparity in post-LT renal dysfunction rates between these studies might arise from differences in pre-LT renal function status, source of graft (LDLT or DDLT), presence of diabetes/hypertension, post-LT care, timing of kidney function monitoring, or definitions used for renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In another study by Kim et al [ 31 ], 43.5% of the overall LT recipients were reported to have moderate renal dysfunction (defined as the 30≤ eGFR <60 mL/min/1.73 m 2 ). The rate of renal dysfunction post-LT varies considerably among recipients in other countries, with 8.0% in Egypt [ 33 ], 48.0% in Spain [ 34 ], and 46.7% in Brazil [ 35 ]. This disparity in post-LT renal dysfunction rates between these studies might arise from differences in pre-LT renal function status, source of graft (LDLT or DDLT), presence of diabetes/hypertension, post-LT care, timing of kidney function monitoring, or definitions used for renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, blood loss during surgery was independently associated with the risk of post-LT AKI in the study of Zongyi et al [ 27 ] as well as in previously published research [ 20 , 23 ]. The role of intraoperative blood loss was also found to be a significant risk factor of chronic RD 1 year after LT in univariate regression analysis of 500 cases [ 41 ]. Recently, Mrzljak et al published Crostians’ data regarding early AKI after LT, indicating the negative role of red blood cell transfusion [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are few reports on the causes of CKD progression and eGFR changes after LDLT, previous reports have suggested that advanced age, low pre-transplant eGFR value, and graft-to-recipient weight ratio as negative predictors were the associated risk factors for CKD progression after LDLT [ 2 , 14 ].…”
Section: Discussionmentioning
confidence: 99%